2013
DOI: 10.1589/jpts.25.3_245
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Exercise Program for Diabetic Patients in Mongolia

Abstract: Abstract.[Purpose] The purpose of this study was to validate the effects of an exercise program developed for healthy Japanese young men. This program was established as a basis for an exercise program for diabetic patients in Mongolia.[Methods] Ten healthy young men underwent the exercise tolerance test. They participated in a light exercise program consisting of 10 stretching exercises and 11 light exercises. During the exercise tolerance test and exercise program, heart rate (HR), oxygen uptake (VO 2 ), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…A four-year study 18 ) reported that the performance of exercise resulted in a statistically significant increase in the speed of conduction through n. peroneus, while the conduction velocity through n. suralis did not significantly change. Several other studies have confirmed these results 19 , 20 , 21 , 22 ) . In our present study, the performance of exercise combined with magnetotherapy and electrotherapy also achieved a significant increase in the speed of conduction through n.peroneus in group B patients, but the application of these physical agents also significantly increased the speed of conduction through n. suralis.…”
Section: Discussionsupporting
confidence: 55%
“…A four-year study 18 ) reported that the performance of exercise resulted in a statistically significant increase in the speed of conduction through n. peroneus, while the conduction velocity through n. suralis did not significantly change. Several other studies have confirmed these results 19 , 20 , 21 , 22 ) . In our present study, the performance of exercise combined with magnetotherapy and electrotherapy also achieved a significant increase in the speed of conduction through n.peroneus in group B patients, but the application of these physical agents also significantly increased the speed of conduction through n. suralis.…”
Section: Discussionsupporting
confidence: 55%
“…This study showed that young adults with a sedentary lifestyle were compliance to the 8-week resistance exercise program. However, further studies are needed to study the long-term effects of resistance exercise on cardiovascular outcomes and its effects in other patient settings 11 , 12 , 13 , 14 , 15 , 16 , 17 ) . The other advantage of this study is that it was a randomized control trial.…”
Section: Discussionmentioning
confidence: 99%